IMPACT OF COVID-19 ON DIFFERENT SECTORS IN INDIA AND SUGGESTIONS TO BOOST INDIAN ECONOMY TO RECOVER FROM THE PANDEMIC. (International Journal of Food and Nutritional Sciences, 2022)
The successful growth of any country is largely depending on citizen’s health. A healthy population contributes to productivity saving and progress. In 1950 India had started remarkable efforts to improve public health. In India increasing population and industrialization increasing environmental problems and consequently there is increasing communicable and non-communicable diseases that not only effect lives of people but also working capacity of various sectors of economy. One such current occurrence is covid-19 diseases. This pandemic firstly affectsChina and China’s economy slowdown. Since it was a communicable disease